Symposium 2: Interpreting Complexity: A case for the sociotechnical interaction framework as an analytical lens for learning technology research - Creanor, Linda; Walker, Steve (Proceedings of the International Conference on Networked Learning, 2010)
In this paper we highlight challenging issues in current learning technology research, particularly in relation to emerging collaborative technologies and the growing body of evidence on the learner experience. The complex nature of the interplay of social, technical and environmental factors is examined along with an overview of the key theoretical models which are currently in play. Limitations are identified in the learning technology literature in which a technological determinism is often evident, despite repeated calls for an approach which takes fuller account of the technology’s pedagogical, organisational, social and technical aspects. We propose that interdisciplinary collaboration has the potential to help us address the demanding task of analysing these interconnected factors, and may also go some way towards mitigating over-charged claims of the impact and effectiveness of learning technology against the reality of its use. The focus of this paper is on sociotechnical approaches, particularly those derived from a social informatics tradition, which to date appear to have received little attention in learning technology research. We identify potential benefits in applying these approaches to today’s learning environment which encompasses fast-moving technology developments along with changing communicative behaviours among learners, whether on campus, in the workplace or in everyday life. Most importantly, sociotechnical frameworks address the issue of technological determinism by explicitly recognising that agency also resides in individual learners, social structures, the design of learning artefacts and context in which the learning takes place. In order to demonstrate the value of such approaches, we go on to outline findings from the application of one of these concepts, namely a sociotechnical interaction network (STIN), to a transnational networked learning context. The paper concludes by proposing that these approaches in general, and the sociotechnical interaction network concept in particular, are important conceptual tools in dealing with issues currently confronting contemporary learning technology research, such as the spread of web 2.0 and mobile technologies and the increasingly complex social and technological contexts of many learners. They may also provide a valuable means of exploring the increasingly blurred distinction between abstract and formal learning, and situated informal learning, particularly in relation to the workplace.